CYP1A2 Gene Polymorphism and Theophylline Level in Asthma - Amelia Lorensia; Zullies Ikawati; Tri Murti Andayani; Daniel Maranatha; Mariana Wahyudi (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Aminophylline (theophylline) is one of the most frequent asthma therapies in Indonesia, although it remains as a narrow therapy. The effects of drugs are individualized and strongly influenced by genetic, one of which is CYP1A2 gene polymorphisms. This study aimed to determine the profile of CYP1A2 polymorphism and theophylline level in asthma exacerbation patients receiving intravenous aminophylline therapy.METHODS: This cross sectional study was conducted in the emergency room (ER), to adults asthma exacerbation patients without complication (n=27), visiting the ER. The gene polymorphism data were compared with theophylline levels in the blood using chi-square test.RESULTS: In the CYP1A2 gene polymorphism profile, the most common heterozygous alleles are T/G genotype of CYP1A2*1E and C/A genotype of CYP1A2*1F. Most homozygote alleles exist in CYP1A2*1D and CYP1A2*1F. There was significant difference between CYP1A2*1D (p<0.005), CYP1A2*1E (p<0.023) and CYP1A2*1F (p<0.000) polymorphisms and theophylline level.CONCLUSION: CYP1A2*1D, CYP1A2*1E and CYP1A2*1F gene polymorphisms had an effect on theophylline levels. However, no one experienced an overdose theophylline, and no correlation between theophylline levels with CYP1A2 gene polymorphism.KEYWORDS: exacerbation asthma, intravenous aminophylline, CYP1A2 polymorphism gene, theophylline